Recent developments in intranasal drug delivery of nanomedicines for the treatment of neuropsychiatric disorders - Kisku, Anglina; Nishad, Ambresh; Agrawal, Saurabh; Paliwal, Rishi; Datusalia, Ashok Kumar; Gupta, Gaurav; Singh, Sachin Kumar; Dua, Kamal; Sulakhiya, Kunjbihari (Frontiers in Medicine, 2024)
Neuropsychiatric disorders are multifaceted syndromes with confounding neurological explanations. It includes anxiety, depression, autism spectrum disorder, attention deficit hyperactivity disorder, schizophrenia, Tourette's syndrome, delirium, dementia, vascular cognitive impairment, and apathy etc. Globally, these disorders occupy 15% of all diseases. As per the WHO, India has one of the largest populations of people with mental illnesses worldwide.The blood-brain barrier (BBB) makes it extremely difficult to distribute medicine to target cells in the brain tissues.However, it is possible through novel advancements in nanotechnology, molecular biology, and neurosciences. One such cutting-edge delivery method, nose-to-brain (N2B) drug delivery using nanoformulation (NF), overcomes traditional drug formulation and delivery limitations. Later offers more controlled drug release, better bioavailability, improved patient acceptance, reduced biological interference, and circumvention of BBB. When medicines are delivered via the intranasal (IN) route, they enter the nasal cavity and go to the brain via connections between the olfactory and trigeminal nerves and the nasal mucosa in N2B. Delivering phytochemical, bioactive and synthetic NF is being investigated with the N2B delivery strategy. The mucociliary clearance, enzyme degradation, and drug translocations by efflux mechanisms are significant issues associated with N2B delivery. This review article discusses the types of neuropsychiatric disorders and their treatment with plant-derived as well as synthetic drug-loaded NFs administered via the IN-delivery system. In conclusion, this review provided a comprehensive and critical overview of the IN applicability of plant-derived NFs for psychiatric disorders.